2020
DOI: 10.1002/term.3003
|View full text |Cite
|
Sign up to set email alerts
|

Engineered skin graft with stromal vascular fraction cells encapsulated in fibrin–collagen hydrogel: A clinical study for diabetic wound healing

Abstract: Despite the abundance of skin substitutes in the worldwide market, major hurdles in developing more complex tissues include the addition of skin appendages and vascular networks as the most important structure. The aim of this research was a clinical feasibility study of a novel prevascularized skin grafts containing the dermal and epidermal layer using the adipose stromal vascular fraction (SVF)‐derived endothelial cell population for vascular network regeneration. Herein, we characterized hydrogel with empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 71 publications
0
49
0
Order By: Relevance
“…In the current study, the appropriate volume and concentration of thrombin were used according to the final volume and concentration of platelet concentrate as well as calcium gluconate; therefore, the formation fibrin network and platelet gel had a suitable density since if the fibrin network has high density and hard structure, the growth factors derived from cord blood platelet do not have a proper release and spread in surface wound area and are trapped in the fibrin network itself and wound healing does not have a good quality. Also, if the concentration and volume of thrombin used are low, the platelet gel is very loose and cannot be adjusted at the wound site 23,29,30 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the appropriate volume and concentration of thrombin were used according to the final volume and concentration of platelet concentrate as well as calcium gluconate; therefore, the formation fibrin network and platelet gel had a suitable density since if the fibrin network has high density and hard structure, the growth factors derived from cord blood platelet do not have a proper release and spread in surface wound area and are trapped in the fibrin network itself and wound healing does not have a good quality. Also, if the concentration and volume of thrombin used are low, the platelet gel is very loose and cannot be adjusted at the wound site 23,29,30 …”
Section: Methodsmentioning
confidence: 99%
“…Platelets are a great source of growth factors such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), transforming growth factor (TGF), and platelet‐derived growth factor (PDGF), all of which play an important role in wound healing, tissue regeneration, and generally in the fields of regenerative medicine. Platelet‐rich plasma of the umbilical cord blood contains a high level of PDGF, which is an important factor in restoration and regeneration of the damaged tissue 20‐23 . This method (preparation of cord blood platelet gel) was studied and evaluated for the first time in Italy 24…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study, we overcame these hurdles by the in vitro generation of capillary networks in DESSs using endothelial and mesenchymal progenitors derived from the stromal vascular fraction (SVF) of human adipose tissue (Figure 2) [12,13,20]. This approach holds great promise for future clinical applications as adipose tissue represents a convenient, abundant, and easily accessible cell source [78]. Moreover, this concept was previously successfully used in the engineering of precisely sized osteogenic constructs, increasing the efficiency and uniformity of bone tissue formation [79].…”
Section: Bioengineered Dermo-epidermal Skin Substitutes (Under Develomentioning
confidence: 99%
“…Further studies have demonstrated the ability of ASCs to modulate mixed lymphocyte reactions in vitro and to display immunosuppressive properties in vivo [ 37 , 38 ]. Through the use of enzymatic isolation methods, independent laboratories have advanced SVF cell and ASC production as current good manufacturing practices (cGMP) to create clinical-grade cell products that are suitable for the treatment of skin wounds, soft tissue cosmesis, or bone defects [ 39 , 40 , 41 , 42 ]. These approaches have relied on the use of the patient’s autologous serum or the use of human platelet lysates for cell culture and expansion [ 43 , 44 ].…”
Section: Adipose-derived Cellsmentioning
confidence: 99%